Customer Complaint Behavior (CCB) in the Hotel Industry- A Perspective of Chennai Customers - Arulkumar, S.; Krithika, M. (International Journal of Psychosocial Rehabilitation, 2019)
Complaint behavior of the customers can be well-defined as an expression of an unfavorable behavioral attitude towards a product, individual, or circumstance (Johnston and Michel, 2008). Consumer complaint behavior (CCB) in marketing is frequently observed either as a fixed activity or as a powerful change process. This subject is still under discussion. According to study by Malhotra, Naresh K., et al., (2008), a service renovation of consumers, will increase loyalty and obtain constructive feedback. The primary purposes of this research paper are to identify the extent of influence of the level of dissatisfaction. The study population consisted of customers visiting hotels located in Chennai to find the answer to the goals. Chennai hotels have been selected based on membership hotels listed under the Chennai branch of the South Indian hotel association. The respondents were selected based on a sampling methodology for non-probability convenience. The questionnaire was to analyze respondents’ complaining of conduct. To measure the behavior of the customers, a structured questionnaire developed by Joseph Tong and Jamie Carlson (2012), Blodgett et al., (1993), Richins (1980), Malhotra, Naresh K., et al., (2008) used. It consists of 31 statements calculated on a five-point Likert scale, with 5 suggesting strong agreement and one strong disagreement. Before check-in or after check-out, the respondents asked to fill out the questionnaires. About 500 questionnaires were circulated from August to November 2019 and received personally. Of these, the study contained 389 surveys. Consequently, the response rate was 77 percent out of the original 500 surveys. For data analysis, SPSS 20.0 was used to obtain the results. Multiple regression used to find out the extent of influence of the variables taken for the study. The results show that all variables significantly influence the CCB experience. The findings, suggestions addressed here can substantially assist the researchers in understanding how consumers take complain of action in case of dissatisfied service.